ANALISIS PENERAPAN SHARIA COMPLIANCE TERHADAP KESEJAHTERAAN UMKM DI BANGKALAN - Nur Zaidah; Ahmad Musadad (PROCEEDING UMSURABAYA, 2022)
ABSTRACT   Indonesia is a country where the majority of the population is Muslim, where their daily activities follow several things that have been regulated and determined based on Islamic sharia law. This is no exception for everyone who applies Sharia Compliance. Sharia compliance is a rule that can be used as a foundation for the continuity of transactions both in banking and other financial institutions. In essence, many people do not really know the meaning of Sharia compliance even though it is often side by side with people's lives as is the case with micro small and medium enterprises. This paper aims to examine whether if sharia compliance is applied to micro small and medium enterprises there is an effect on the welfare of both Micro small and medium enterprises themselves and employees. Therefore, the existence of micro small and medium enterprise is very vital in people's lives, especially in daily life. Judging from some of the data needed regarding micro small and medium enterprises to know the implementation of sharia compliance for the welfare of the community. So that researchers have an interest in several micro small and medium enterprises that from the start have implemented Sharia compliance for the welfare of their employees. In this study, the sample used was 5 Micro small and medium enterprises in Bangkalan. In the preparation of this study, the researcher used qualitative research methods with sociological normative research, namely by searching Islamic law literature and then relating it to the facts found in the field. To support the acquisition of data, the researchers also made observations and went directly to the field, so that the data obtained were real without any composition.Keywords                   : Sharia Compliance; Prosperity; Micro small and medium enterprises